2005
DOI: 10.1055/s-2005-837553
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Connection Between the Presence of Kidney Stones in Primary Hyperparathyroidism and the Location of an Underlying Adenoma?

Abstract: The majority of the patients with primary hyperparathyroidism (pHPT) recurrently produce kidney stones, while the rest have other clinical manifestations. The aim of this study was to examine the possibility of an association between the presence of kidney stones and the location of an underlying adenoma. This was a retrospective evaluation of the records of 91 patients (10 males, 81 females, mean age: 61.9 years [20 - 70 yrs]) operated for primary hyperparathyroidism between 1995 and 2000. One patient was exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Using values for the urinary calcium to creatinine ratio, and serum calcium and creatinine concentrations [10] Csupor et al. found 3.3% FECa in HPT, vs the present value of 1.92%.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Using values for the urinary calcium to creatinine ratio, and serum calcium and creatinine concentrations [10] Csupor et al. found 3.3% FECa in HPT, vs the present value of 1.92%.…”
Section: Discussionmentioning
confidence: 85%
“…[9] found a mean of 10.9 mg/dL in 27 cases, Csupor et al. [10] found a mean of 12 mg/dL among 55 cases. The weighted mean for all 338 cases, excluding those of Mallette et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their series of 90 patients with surgically treated PHPT showed that 91% of those with kidney stones had adenomas in the left inferior parathyroid gland, and 69% of those without kidney stones had adenomas in the right inferior gland. They suggested that perhaps distinct active PTH fragments may be made from different parathyroid glands 10 . They did not, however, speculate regarding the autonomous versus suppressible nature of the adenomas based on location in the neck, nor did they analyze patients with hyperplasia rather than adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that perhaps distinct active PTH fragments may be made from different parathyroid glands. 10 They did not, however, speculate regarding the autonomous versus suppressible nature of the adenomas based on location in the neck, nor did they analyze patients with hyperplasia rather than adenoma.…”
Section: Discussionmentioning
confidence: 99%